Laparoscopic cholecystectomy in children - A. G. Zaporozhchenko; A. E. Solovjov,; A. P. Gladkyy; O. V. Spakhi (Zaporožskij Medicinskij Žurnal)
Introduction. laparoscopic cholecystectomy is the “gold standard” of the calculous cholecystitis treatment, opening absolutely new stage.